Adaptive Reuse as a Tool for Sustainable Urban Development: The Case Study of Singapore, Southeast Asia - Cudicio, Yaelle; Bassols i Gardella, Narcís (Journal of Urban Culture Research, 2024)
This article aims to explore the application of adaptive reuse as a tool for urban built heritage management through the study of five cases in the city of Singapore, Southeast Asia. At the crossroads of urban strategy, building conservation and heritage management, the cases reveal the complexities of contemporary urban developments in one of the world’s leading cities. Five projects are analyzed and compared via thematic and content analysis, drawing from primary and secondary sources. The cases display the potential of adaptive reuse, as well as their connection to the larger context of sustainable urban (re)development, while offering a realistic overview of the possible difficulties associated with this process, such as gentrification and over-commercialization. Ultimately, the authors argue for adaptive reuse as a tool to be considered by built heritage managers and urban developers, as it may strike the right balance between different stakeholders and objectives.